The library ghost - Weatherford, Carole; White, Lee 1970- (Fort Atkinson, Wis. : Upstart Books, 2008)
At night, a ghost visits the library to find the answer to a riddle.
Keywords: Librarians; Libraries; Ghosts; Stories in rhyme